Water Quality of a Tributary of Siak River and Reservoir in Pekanbaru City, Riau Province, Using the CCME-WQI - Yuliati Yuliati; Eni Sumiarsih; Adriman Adriman; Nurfatihayati Nurfatihayati; Efawani Efawani (Depik, 2024)
This research was conducted on one of the Siak River tributaries that crosses the urban area in Pekanbaru, namely the Pengambang River. The Pengambang River flow is dammed to become a reservoir; one of its functions is as a source of raw drinking water. Increased activity along rivers and reservoirs certainly has an impact on water quality. The research was carried out in May-October 2023. Water sampling was taken at 3 points each along the river flow and in the Reservoir. The physicochemical water quality parameters measured include temperature, TSS, BOD, COD, DO, pH, TP, Nitrate, and Total coliforms for rivers and reservoirs, while Chorofil-a only for reservoirs. Water quality was evaluated using CCME-WQI, and the results of water quality evaluation according to CCME-WQI in the Pengambang River at all sampling stations could have been bad to marginal. At the same time, in the Reservoir, it was marginal. The CCME_WQI Index value in rivers ranges 42.33 to 54.97, while in reservoirs, it is higher 49-56, it indicated water quality in reservoir better than river. Parameters influencing water quality in rivers and reservoirs, especially TC and BOD come from household waste cage fish cultivation.